2016
DOI: 10.1007/s11999-015-4412-9
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Intraoperative MRI Suite for the Musculoskeletal Tumor Center

Abstract: Background Altered anatomy in a previously irradiated surgical bed can make accurate localization of anatomic landmarks and local recurrence nearly impossible. The use of intraoperative MRI (iMRI) has been described in neurosurgical settings, but to our knowledge, no such description has been made regarding its utility for local recurrence localization in sarcoma surgery. Case Description A 58-year-old female presented after previously undergoing two previous resection and reresection procedures of a myxoid li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The authors attribute these differences to the inherent limitations of our current mp-MRI sequences, which are optimized for lesion detection and not staging, and significant interobserver variability in Gleason histological grading. 5,6 These findings highlight few critical points concerning the adoption of MRI/US fusion prostate biopsy in our clinics. First, the accuracy of the fusion biopsy is not sufficient to forego the conventional systematic biopsy at the present time.…”
Section: Editorial Commentmentioning
confidence: 88%
“…The authors attribute these differences to the inherent limitations of our current mp-MRI sequences, which are optimized for lesion detection and not staging, and significant interobserver variability in Gleason histological grading. 5,6 These findings highlight few critical points concerning the adoption of MRI/US fusion prostate biopsy in our clinics. First, the accuracy of the fusion biopsy is not sufficient to forego the conventional systematic biopsy at the present time.…”
Section: Editorial Commentmentioning
confidence: 88%
“…Kwon et al ( 11 ) demonstrated that there was a relatively high concordance in tumor thickness between MRI and histopathology in patients with oral tongue squamous cell carcinoma. With the progressive development of intraoperative MRI, surgeons have tried to use intraoperative MRI to guide the resection of soft tissue sarcoma to reduce the re-resection rates ( 12 , 13 ). On the other hand, MRI with or without enhanced contrast has made noteworthy progress in perforator mapping in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…The only cost to the patient is the cost of the surgery plus the cost of the MRI scan (approximately $286). However, to the best of our knowledge, there are only two reports to date describing the use of iMRI for musculoskeletal tumors (17,18) and none focusing on GCTB resection after denosumab therapy. We hypothesized that iMRI could be used to identify residual tumor tissue, thus enabling successful curettage.…”
Section: Introductionmentioning
confidence: 99%